Environment and time drive the links between the species richness and ecosystem multifunctionality from multitrophic freshwater mesocosms - Xu, Zhiyan; Yang, Hui; Mao, Hongzhi; Peng, Qiutong; Yang, Shiwen; Chou, Qingchuan; Yang, Yujing; Li, Zhongqiang; Wei, Lifei (Frontiers in Marine Science, 2023)
Understanding link between biodiversity and ecosystem functioning is imperative in allowing ecosystem-based management. However, the role of multitrophic diversity in sustaining multifunctionality remains unclear, especially in highly diverse aquatic ecosystems. We performed a species-addition experiment, consisting of 1, 2, 3, and 5 species, to evaluate biodiversity and ecosystem functioning relationship within and across trophic levels. Our results showed that there are positive species richness-productivity relationships within and across trophic levels. Instead, we found significant negative correlations between species richness and the amount of TP cumulative variation, and between species richness and ecosystem multifunctionality across trophic levels. Also, we found that the links between ecosystem multifunctionality and biodiversity within and across the trophic levels are mediated by the combination of environmental factors and time, rather than by species richness. Our results imply that different biodiversity and ecosystem functioning relationships for different ecosystem functions and importance of selected individual ecosystem functioning and calculated method of ecosystem multifunctionality for biodiversity and ecosystem multifunctionality relationship research. Our study highlights that multitrophic richness such as consumers are crucial moderators in driving ecosystem multifunctionality. Also, our study imply that management practices of restoring the diversity of aquatic macrophyte in wetlands should consider not only macrophyte richness, but also different functional groups and life-forms.